Lost in Transition: Puzzles of Reconciliation - Ólafsson, Jón (Res Cogitans, 2015)
This paper discusses reconciliation as a strategy to heal social wounds caused by dictatorial regimes or deep economic crises. The paper treats two such examples: The failed attempts of the Icelandic government to reach a deal with the UK and the Netherlands about the repayment of debts incurred by the bankrupt Landsbanki Íslands and the prosecution of Mr. Geir Haarde, formerly Prime Minister of Iceland. It is argued that although reconciliation strategies have in some cases been partially successful, it can be counterproductive to prefer moral aspirations or goals, such as rebuilding trust after serious political, social or economic disintegration, to strictly legal ways of dealing with individual cases. As the case with Mr. Haarde shows, the endeavor to achieve moral goals using legal means can backfire in unexpected ways.